2020
DOI: 10.1002/prp2.626
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of steroids in reducing morbidity and mortality from extreme hyperthermia and heatstroke—A systematic review

Abstract: Hyperthermia induces deleterious effects at the cellular, organ, and whole-body level, 1 and has a variety of causes, which include sepsis, classical and exertional heat illness, and drug-induced hyperthermia. While there is a survival benefit to a mild pyrexia in sepsis, 2,3 mortality increases as the core temperature (T CORE) exceeds 40°C, 2 suggesting that at higher temperatures, the deleterious effects on organ and cellular function outweigh any benefit conferred from pyrexia. In noninfective hyperthermia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…Future work should seek to quantify these responses against baseline/control L:R and data from a normothermic exercise trial, and investigate pharmacological and nutritional-or hydration-related interventions to mitigate against heat stress. Strategies to reduce GI permeability, endotoxemia, and/or organ dysfunction have shown promising results via prior-exercise glutamine ingestion (Pugh et al, 2017); mid-exercise carbohydrate and protein intake (Snipe et al, 2017), and in animals, the administration of steroid (Walter & Gibson, 2020a) and antibiotics (Walter & Gibson, 2020b) following the development of exertional heat stress. This work should extend to a heterogeneous cohort of participants likely to be exposed to passive heat or EHI across a spectrum of thermal and exercise stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should seek to quantify these responses against baseline/control L:R and data from a normothermic exercise trial, and investigate pharmacological and nutritional-or hydration-related interventions to mitigate against heat stress. Strategies to reduce GI permeability, endotoxemia, and/or organ dysfunction have shown promising results via prior-exercise glutamine ingestion (Pugh et al, 2017); mid-exercise carbohydrate and protein intake (Snipe et al, 2017), and in animals, the administration of steroid (Walter & Gibson, 2020a) and antibiotics (Walter & Gibson, 2020b) following the development of exertional heat stress. This work should extend to a heterogeneous cohort of participants likely to be exposed to passive heat or EHI across a spectrum of thermal and exercise stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The survival benefit was most significant when steroid administration preceded heat stress. 69 As for antipyretics, there is no evidence supporting the use of nonsteroidal antiinflammatory drugs in heatstroke. 70 Neural injury is a significant issue in heatstroke, and mesenchymal stem cell transplantation has been reported to improve neurological function, and its efficacy and molecular mechanisms have been intensively investigated.…”
Section: Treatment For Non-exertional Heatstrokementioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs (NSAIDs), aspirin, and acetaminophen are ineffective and could exacerbate end-organ damage [ 46 , 67 , 69 ]. Dantrolene is not routinely effective, although small studies suggest benefits in combination with cooling [ 46 , 70 ]. Corticosteroids may reduce pro-inflammatory cytokines.…”
Section: Reviewmentioning
confidence: 99%
“…A recent meta-analysis of animal studies found that they reduced morbidity and mortality. However, applying this steroid data to humans remains controversial [ 70 ]. Older animal trials evaluated the efficacy of oral prophylactic antibiotics.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation